Learning Tableau 2022 Create effective data visualizations, build interactive visual analytics, and improve your data storytelling capabilities - Milligan, Joshua N.; Milligan, Joshua N.; Hutchinson, Blair; Tossell, Mark (Packt Publishing, 2022)
Now in color, this edition of Learning Tableau will empower you to bring data to life and make better business decisionsKey FeaturesLearn the basics of data analysis, from snappy visualizations to comprehensive dashboardsGain meaningful insights with geospatial analysis, scripting extensions, and other advanced methodsExplore the latest Tableau 2022 features, including Einstein Discovery and Explain DataBook DescriptionLearning Tableau 2022 helps you get started with Tableau and data visualization, but it does more than just cover the basic principles. It helps you understand how to analyze and communicate data visually, and articulate data stories using advanced features.This new edition is updated with Tableau's latest features, such as dashboard extensions, Explain Data, and integration with CRM Analytics (Einstein Analytics), which will help you harness the full potential of artificial intelligence (AI) and predictive modeling in Tableau.After an exploration of the core principles, this book will teach you how to use table and level of detail calculations to extend and alter default visualizations, build interactive dashboards, and master the art of telling stories with data.You'll learn about visual statistical analytics and create different types of static and animated visualizations and dashboards for rich user experiences. We then move on to interlinking different data sources with Tableau's Data Model capabilities, along with maps and geospatial visualization. You will further use Tableau Prep Builder's ability to efficiently clean and structure data.By the end of this book, you will be proficient in implementing the powerful features of Tableau 2022 to improve the business intelligence insights you can extract from your data.What you will learnDevelop stunning visualizations to explain complex data with clarityBuild interactive dashboards to drive actionable user insightsExplore Data Model capabilities and interlink data from various sourcesCreate and use calculations to solve problems and enrich your analyticsEnable smart decision-making with data clustering, distribution, and forecastingExtend Tableau's native functionality with extensions, scripts, and AI through CRM Analytics (formerly Einstein Analytics)Leverage Tableau Prep Builder's amazing capabilities for data cleaning and structuringShare your data stories to build a culture of trust and actionWho this book is forThis Tableau book is for aspiring BI developers and data analysts, data scientists, researchers, and anyone else who wants to gain a deeper understanding of data through Tableau. This book starts from the ground up, so you won't need any prior experience with Tableau before you dive in, but a full Tableau license (or 14-day demo license) is essential to be able to make use of all the exercises.